2011
DOI: 10.1590/s0066-782x2011005000079
|View full text |Cite
|
Sign up to set email alerts
|

Trimetazidina na injúria de isquemia e reperfusão em cirurgia de revascularização do miocárdio

Abstract: ResumoFundamento: A injúria de isquemia e reperfusão constitui um mecanismo fisiopatológico frequente e de difícil controle durante a Cirurgia de Revascularização do Miocárdio (CRVM) com circulação extracorpórea, sendo o momento crítico o término da cirurgia, quando ocorre o desclampeamento da aorta e a liberação dos radicais hiperóxidos causadores da injúria.Objetivo: Avaliar, em estudo prospectivo, duplo-cego randomizado, controlado com placebo, os efeitos da Trimetazidina (Tmz) sobre a injúria de isquemia e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…When extending the analysis to compare the Tmz and placebo groups of this study with those of the study by Martins et al 6 , those variables showed no significant difference.…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…When extending the analysis to compare the Tmz and placebo groups of this study with those of the study by Martins et al 6 , those variables showed no significant difference.…”
Section: Discussionmentioning
confidence: 63%
“…Martins et al 6 have assessed 137 patients with echocardiographic indication for CABG-ECC, 75 of whom, with normal ventricular function or mild dysfunction, were selected. Of those, 60 patients, distributed in the treated and placebo groups, completed the tests for the serum markers of myocardial injury (troponin-T and CPK-MB).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations